2019
DOI: 10.5194/isprs-archives-xlii-4-w19-401-2019
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll-a Concentration Retrieval Using Convolutional Neural Networks in Laguna Lake, Philippines

Abstract: Abstract. Two existing chlorophyll-a (chl-a) concentration retrieval procedures, which are analytical and empirical, are hindered by the complexity in radiative transfer equation (RTE) and in statistical analyses, respectively. Another promising model in this direction is the use of artificial neural networks (ANN). Mostly, a pixel-to-pixel with one-layer ANN model is used; where in fact that the satellite instrumental errors and man-made objects in water bodies might affect the retrieval and should be taken i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The study also revealed that the optimal ANN model outclassed the other machine learning methods, including random forest, cubist regression, and support vector regression, in terms of Chla concentration estimation. Furthermore, several researchers utilized convolutional neural networks (CNNs), which consider neighborhood spectral information in Chla concentration modelling using convolutional layers with 3D kernels [26][27][28][29].…”
Section: More Than 56mentioning
confidence: 99%
“…The study also revealed that the optimal ANN model outclassed the other machine learning methods, including random forest, cubist regression, and support vector regression, in terms of Chla concentration estimation. Furthermore, several researchers utilized convolutional neural networks (CNNs), which consider neighborhood spectral information in Chla concentration modelling using convolutional layers with 3D kernels [26][27][28][29].…”
Section: More Than 56mentioning
confidence: 99%
“…Several studies have also investigated the case of Chl-a concentration in Laguna Lake. Specifically, Blanco et al (2020) used regression analysis of Sentinel-3 OLCI images to produce algal classification maps, Syariz et al (2019) used neural networks trained on the same Sentinel-3 data to produce models that out-perform existing 3-band and 2-band models in terms of accuracy, and Jalbuena et al ( 2019) inputted Landsat-8 data in the Bio-Optical Model Based tool for Estimating water quality and bottom properties from Remote sensing images (BOMBER) tool and processed this data through the Water Color Simulator (WASI) tool to produce Chl-a maps.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial neural networks (ANNs) have been utilized in geospatial fields with various applications [8,[38][39][40]. ANN is called glorified regression because of the network's nonlinear modeling feature.…”
Section: Introductionmentioning
confidence: 99%